Verification and analysis of a Battery Energy Storage System model. (November 2022) - Hutchinson, Andrew J.; Gladwin, Daniel T.
Abstract: Energy Storage System modelling is the foundation for research into the deployment and optimization of energy storage in new and existing applications. The increasing penetration of renewable energy into electrical grids worldwide means energy storage is becoming a vital component in the modern electrical distribution system. In this paper, a model for a Battery Energy Storage System developed in MATLAB/Simulink is introduced and subsequently experimentally verified against an existing 2 MW installation operated by The University of Sheffield (Willenhall). The model presented in this paper achieved average Root Mean Square Error (RMSE) values of 1.29% and 1.05% when comparing the state of charge (SOC) of the model with two different methods of SOC measurement at the Willenhall installation. The methodology behind fine tuning the model to decrease the average RMSE is presented and discussed.